Program konseling melalui website pada siswa korban perundungan dengan metode cognitive behavior therapy di SMA Negeri 4 Mataram - Choirunnisa; I Gusti Ayu Maesya Andini; Ristania Tri Widiarti; I Putu Ananta Sugiartha; Ahmad Bawazir Jazuli; Nourma Pramestie Wulandari (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
The intensity of bullying in Indonesia is increasing as time goes by. Especially in the digital era with very rapid technological developments causing an increase in criminal acts and cyberbullying. Now bullying can not only occur directly in the school environment but can also occur through social media. Bullying behavior often occurs at school. This becomes a detrimental problem for the victim because they are affected by bullying. So school leaders are trying hard to overcome it. From these conditions, a concrete effort emerged to overcome bullying and help victims affected by bullying, namely by providing a forum for therapeutic counseling and reporting regarding bullying in web form using the Cognitive Behavior Therapy (e-CBT) method which is easily accessible to students and victims of bullying. In the hope of helping victims affected by bullying. Through this website, they gain exposure to knowledge regarding the meaning and legal articles that can be used to catch perpetrators of bullying as well as the types of bullying and how to deal with it. Apart from that, therapy containers are also provided in the form of filling in for reporting bullying experienced.